Effect of change factors on evaporation loss based on cold end system in natural draft counter-flow wet cooling towers - Wei YUAN; Fengzhong SUN; Ruqing LIU; Xuehong CHEN; Ying LI (Journal of Thermal Science and Technology, 2021)
The water loss caused by evaporation heat dissipation is non-negligible for a natural draft counter-flow wet cooling tower (NDWCT), which is evidently influenced by many change factors. Based on Merkel method, the Merkel number is revised in consideration of the effect of water loss. Taking the NDWCTs equipped for 300MW and 600MW power plants as experimental objects, a mathematical model is established for predicting the evaporation loss of the NDWCT. The accuracy of the model is verified by experimental data, and the mathematical model for predicting evaporation loss is feasible. Then, the effect of change factors, including mass flow rate of circulating water and air parameters, on the tower evaporation loss is studied in the case of fixed the thermal load dissipated by the condenser. Results show that the evaporation loss varies little with the change of mass flow rate of circulating water. Therefore, Water conservation cannot be achieved by changing mass flow rate. With the increase of dry bulb temperature, the evaporation loss, as well as the rate of evaporation loss caused by unit temperature drop increases. As the relative air humidity increases, the NDWCT outlet water temperature increases, whereas the evaporation loss and the rate of evaporation loss caused by unit temperature difference decrease.